Cu carbonyls enhance the performance of Ru-based SILP water-gas shift catalysts: a combined in situ DRIFTS and DFT study - Blaumeiser, Dominik; Stepic, Robert; Wolf, Patrick; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Bauer, Tanja; Libuda, Jörg (Catalysis: Science and Technology, 2020)
Ru-based supported ionic liquid phase (SILP) catalysts efficiently promote the water-gas shift reaction (WGSR). The addition of CuCl further improves the performance. This is attributed to the formation of labile Cu carbonyl species, which act as CO shuttles in the ionic liquid (IL) phase. We apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) to monitor the formation of these Cu carbonyls in an imidazolium-based SILP system. To aid the identification of the relevant Cu carbonyls, we perform density functional theory (DFT) calculations. In the present study, we investigate [Ru(CO)(3)Cl-2](2)/CuCl/[C(4)C(1)C(1)Im]Cl/Al2O3 and CuCl/[C(4)C(1)C(1)Im]Cl/Al2O3 with various CuCl : IL ratios. The relevant Cu carbonyls are identified as neutral CuCl monomers and dimers, as well as monoanionic monomers and dimers. Moreover, we demonstrate that the ratio of the individual Cu carbonyl species depends on the CuCl : IL ratio.
CRIS-Team WoS Importer:2020-01-17

Dynamic equilibria in supported ionic liquid phase (SILP) catalysis: in situ IR spectroscopy identifies [Ru(CO)xCly]n species in water gas shift catalysis - Bauer, Tanja; Stepic, Robert; Wolf, Patrick; Kollhoff, Fabian; Karawacka, Weronica; Wick, Christian; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Suncana; Libuda, Jörg (Catalysis: Science and Technology, 2018)
Ru-based supported ionic liquid phase (SILP) systems efficiently catalyze the low-temperature water-gas shift reaction (WGSR). While previous studies suggest that Ru-carbonyl species play an important role in the mechanism, detailed knowledge on the catalytically active species is still missing. To identify these carbonyl complexes, we apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT). Investigations of an as-prepared [R(CO)3Cl2]2/ [C4C1C1Im]Cl/Al2O3 catalyst indicate splitting of the dimer induced by Cl−. Subsequently, an equilibrium between several [R(CO)xCly]n species is established, in which the IL serves as an effectively infinite Cl− reservoir. We find that the major species in the system freshly-prepared from [R(CO)3Cl2]2 is indeed [R(CO)3Cl3]−. A smaller amount of [R(CO)2Cl3]− and chloride-rich species [R(CO)2Cl4]2− or [RuCOCl4]2− are also found in the SILP. Similar Ru-carbonyl species are observed during carbonylation of RuCl3/ [C4C1C1Im]Cl/Al2O3, another potential WGSR catalyst. The response of [Ru(CO)3Cl2]2/[C4C1C1Im]Cl/Al2O3 to heating and/or CO dosing was probed in situ and the results confirm the presence of the equilibrium proposed above.
Keywords: SILP catalysis; in situ IR spectroscopy; [Ru(CO)xCly]n species

Improving the Performance of Supported Ionic Liquid Phase Catalysts for the Ultra-Low-Temperature Water Gas Shift Reaction Using Organic Salt Additives - Wolf, Patrick; Wick, Christian; Mehler, Julian; Blaumeiser, Dominik; Schötz, Simon; Bauer, Tanja; Libuda, Jörg; Smith, David M.; Smith, Ana-Suncana; Haumann, Marco (ACS Catalysis, 2022)
The water gas shift reaction (WGSR) is catalyzed by supported ionic liquid phase (SILP) systems containing homogeneous Ru complexes dissolved in ionic liquids (ILs). These systems work at very low temperatures, that is, between 120 and 160 °C, as compared to >200 °C in the conventional process. To improve the performance of this ultra-low-temperature catalysis, we investigated the influence of various additives on the catalytic activity of these SILP systems. In particular, the application of methylene blue (MB) as an additive doubled the activity. Infrared spectroscopy measurements combined with density functional theory (DFT) calculations excluded a coordinative interaction of MB with the Ru complex. In contrast, state-of-the-art theoretical calculations elucidated the catalytic effect of the additives by non-covalent interactions. In particular, the additives can significantly lower the barrier of the rate-determining step of the reaction mechanism via formation of hydrogen bonds. The theoretical predictions, thereby, showed excellent agreement with the increase of experimental activity upon variation of the hydrogen bonding moieties in the additives investigated.
CRIS-Team Scopus Importer:2022-06-03
Keywords: electronic interaction; methylene blue; ruthenium; supported ionic liquid phase; water gas shift reaction

Improving the performance of supported ionic liquid phase (SILP) catalysts for the ultra-low-temperature water-gas shift reaction using metal salt additives - Wolf, Patrick; Aubermann, Manfred; Wolf, Moritz; Bauer, Tanja; Blaumeiser, Dominik; Stepic, Robert; Wick, Christian; Smith, David M.; Smith, Ana-Suncana; Wasserscheid, Peter; Libuda, Jörg; Haumann, Marco (Green Chemistry, 2019)
Supported ionic liquid phase (SILP) catalyst systems containing homogeneous Ru complexes dissolved in ionic liquids (ILs) catalyze the water-gas shift reaction (WGSR) at very low temperatures, i.e., between 120 and 160 °C. One limiting factor of the SILP WGS technology is the low solubility of CO in most ILs. To overcome this issue, we study the influence of different transition metal chloride additives on the activity of Ru-based WGS SILP catalysts. CuCl as the additive was found to enhance the activity by almost 30%. This increase in activity peaks at a CuCl addition of 4 M as a result of the interplay between the increasing CO uptake in the ionic liquid film as evidenced by means of CO sorption and thermogravimetry, and the increasing, unfavorable ionic liquid acidity at too high CuCl concentrations. The respective chlorocuprate species were identified by means of in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT) calculations. We attribute the enhanced catalytic performance to cuprate ions that act as CO shuttles within the ionic liquid film.
CRIS-Team Scopus Importer:2019-09-27

Materials with Hierarchical Porosity Enhance the Stability of Infused Ionic Liquid Films - Galvan, Yaraset; Bauernfeind, Johannes; Wolf, Patrick; Zarraga, Ramon; Haumann, Marco; Vogel, Nicolas (ACS Omega, 2021)
Defined surface functionalities can control the properties of a material. The layer-by-layer method is an experimentally simple yet very versatile method to coat a surface with nanoscale precision. The method is widely used to either control the chemical properties of the surface via the introduction of functional moieties bound to the polymer or create nanoscale surface topographies if one polymeric species is replaced by a colloidal dispersion. Such roughness can enhance the stability of a liquid film on top of the surface by capillary adhesion. Here, we investigate whether a similar effect allows an increased retention of liquid films within a porous surface and thus potentially increases the stability of ionic liquid films infused within a porous matrix in the supported ionic liquid-phase catalysis. The complex geometry of the porous material, long diffusion pathways, and small sizes of necks connecting individual pores all contribute to difficulties to reliably coat the required porous materials. We optimize the coating process to ensure uniform surface functionalization via two steps. Diffusion limitations are overcome by force-wetting the pores, which transports the functional species convectively into the materials. Electrostatic repulsion, which can limit pore accessibility, is mitigated by the addition of electrolytes to screen charges. We introduce nanoscale topography in microscale porous SiC monoliths to enhance the retention of an ionic liquid film. We use gamma-Al2O3 to coat monoliths and test the retention of 1-butyl-2,3-dimethylimidazolium chloride under exposure to a continuous gas stream, a setup commonly used in the water-gas shift reaction. Our study showcases that a hierarchical topography can improve the stability of impregnated ionic liquid films, with a potential advantage of improved supported ionic liquid-phase catalysis.
CRIS-Team WoS Importer:2021-09-03

Monolithic membrane reactors based on supported ionic liquid phase (SILP) materials – hydroformylation and water-gas shift case studies - Schörner, Markus; Wolf, Patrick; Haumann, Marco (Green Chemical Engineering, 2021)
CRIS-Team Scopus Importer:2024-12-16

Multi-walled carbon nanotube-based composite materials as catalyst support for water-gas shift and hydroformylation reactions - Wolf, Patrick; Logemann, Morten; Schörner, Markus; Keller, Laura; Haumann, Marco; Wessling, Matthias (RSC Advances, 2019)
In times of depleting fossil fuel reserves, optimizing industrial catalytic reactions has become increasingly important. One possibility for optimization is the use of homogenous catalysts, which are advantageous over heterogeneous catalysts because of mild reaction conditions as well as higher selectivity and activity. A new emerging technology, supported ionic liquid phase (SILP), was developed to permanently immobilize homogeneous catalyst complexes for continuous processes. However, these SILP catalysts are unable to form freestanding supports by themselves. This study presents a new method to introduce the SILP system into a support made from multi-walled carbon nanotubes (MWCNT). In a first step, SILP catalysts were prepared for hydroformylation as well as low-temperature water-gas shift (WGS) reactions. These catalysts were integrated into freestanding microtubes formed from MWCNTs, with silica (for hydroformylation) or alumina particles (for WGS) incorporated. In hydroformylation, the activity increased significantly by around 400% when the pure MWCNT material was used as SILP support. An opposite trend was observed for WGS, where pure alumina particles exhibited the highest activity. A significant advantage of the MWCNT composite materials is the possibility to coat them with separation layers, which allows their application in membrane reactors for more efficient processes.
CRIS-Team Scopus Importer:2019-09-17

Tailored monolith supports for improved ultra-low temperature water-gas shift reaction - Portela, Raquel; Wolf, Patrick; Marinkovic, Jakob M.; Serrano-Lotina, Ana; Riisager, Anders; Haumann, Marco (Reaction Chemistry & Engineering, 2021)
Supported ionic liquid-phase (SILP) particulate catalysts consisting of Ru-complexes dissolved in an ionic liquid that is dispersed on a gamma-alumina porous substrate facilitate the water-gas shift (WGS) reaction at ultra-low temperatures. In this work, a screening of different ceramic support materials was performed to design a suitable monolithic support to disperse the SILP system with the objective of scaling up the WGS process efficiently. gamma-Alumina-rich channeled monoliths were developed with the use of natural clays as binders (10 wt% bentonite and 20 wt% sepiolite) with the following properties: i) high volume of mesopores to maximize the catalyst loading and successfully immobilize the ionic liquid-catalyst system via capillary forces, ii) mechanical resistance to withstand the impregnation process and the reaction operating conditions, and iii) surface chemistry compatible with a highly active and selective phase for WGS. The developed monolithic-SILP catalyst demonstrated high stability and long-term WGS performance at 130 degrees C with an average steady-state CO conversion of around 30% after 190 h time-on-stream (TOS) and a conversion of 23% after 320 h TOS. Interestingly, the catalyst activity proved essentially unaffected by variation in the water partial pressure during operation due to accumulation of water in the monolith, thus making the system highly durable.
CRIS-Team WoS Importer:2021-08-27

Ultra-low temperature water-gas shift reaction catalyzed by homogeneous Ru-complexes in a membrane reactor - membrane development and proof of concept - Logemann, Morten; Wolf, Patrick; Loipersböck, Jürgen; Schrade, Alexander; Wessling, Matthias; Haumann, Marco (Catalysis: Science and Technology, 2021)
A monolithic membrane reactor combining the supported ionic liquid-phase (SILP) catalyzed ultra-low temperature water-gas shift reaction (WGSR) within situproduct removal is presented. The SILP catalyst consists of the transition metal complex [Ru(CO)3Cl2]2homogeneously dissolved in 1-butyl-2,3-dimethylimidazolium chloride [C4C1C1Im]Cl and supported on alumina pellets. These Ru-SILP pellets are deposited inside the channels of a silicon carbide monolith. The resulting monolithic catalyst is very active and stable in the WGSR in the temperature range between 120 and 160 °C, thereby making full use of the high equilibrium conversion at these conditions. A facilitated transport membrane was coated onto the smooth outside of the SiC monolith to allow preferential removal of CO2compared to H2. The proof of this concept has been shown under industrially relevant conditions using a biogas feed. These results demonstrate, for the first time, the combination of homogeneous SILP catalyzed WGSR with enhancedin situremoval of one of the products (here: CO2)viafacilitated transport membrane separation.
CRIS-Team Scopus Importer:2021-03-19